Penerapan Pajak Karbon di Indonesia: Kajian Ekonomi, Politik, Dan Sosial - Nabilah Adyana (Pusat Riset dan Inovasi Nasional, 2024)
Climate change poses one of the most urgent global challenges, primarily driven by the increase in greenhouse gas (GHG) emissions, notably carbon dioxide (CO2). Indonesia, as a significant emitter of GHGs, faces severe consequences from climate change. The implementation of a carbon tax emerges as a strategic solution to curb emissions and support global climate mitigation efforts. Economically, the prospects of carbon taxation in Indonesia are promising, with the potential tax revenue acting as a crucial income source and providing financial incentives for transitioning to a low-carbon economy. Political support is pivotal, with awareness of the urgency of climate change and government commitments being key to successful carbon tax implementation. However, political challenges, including resistance from certain industrial sectors and concerns about short-term economic impacts, present serious obstacles. Effective political coordination and diplomacy are essential to overcome these hurdles. Socially, safeguarding low-income households from the cost burdens of a carbon tax is imperative through redistributive policies or targeted protection. Conversely, the implementation of a carbon tax also presents opportunities by creating jobs in the clean energy sector, enhancing societal well-being. Overall, the application of a carbon tax in Indonesia necessitates a holistic approach, considering economic, political, and social aspects. Success relies on effective coordination among the government, industries, and the public, maintaining a balance between social protection and sustainable economic development. Carbon taxation emerges as an instrument not only focused on emission reduction but also on fostering inclusive and sustainable economic growth.